2021
DOI: 10.1007/s00170-020-06563-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of locations on the build tray on the quality of specimens in powder bed additive manufacturing

Abstract: In this study, the effect of powder spreading direction was investigated on selectively laser-melted specimens. The results showed that the metallurgical properties of the specimens varied during fabrication with respect to their position on the build tray. The density, porosity, and tensile properties of the Co–Cr–W–Mo alloy were investigated on cuboid and tensile specimens fabricated at different locations. Two different significant positions on the tray were selected along the powder spreading direction. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“… Infill density [%]: Infill provides internal support for top layers, which would otherwise have to bridge over the empty space. Most products can be printed with 10-15% infill [ 48 ]. Nozzle temperature [°C]: Temperature for melting filament.…”
Section: Resultsmentioning
confidence: 99%
“… Infill density [%]: Infill provides internal support for top layers, which would otherwise have to bridge over the empty space. Most products can be printed with 10-15% infill [ 48 ]. Nozzle temperature [°C]: Temperature for melting filament.…”
Section: Resultsmentioning
confidence: 99%
“…During the powder layer deposition, the weight force of the powder decreases above the current powder layer as the recoater arm moves along the build platform. As this weight force decreases, the powder layer being deposited may be unevenly distributed across the build platform resulting in different packing efficiencies [9]. Moreover, when deciding on a layer thickness to be used, the upper threshold of the powder's particle size distribution (PSD) should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The PBD distribution was measured across the build platform and showed that the PBD increased as the distance from the powder supply chamber increased. In terms of part density distribution across the build platform, Pal et al [9] analysed the density, porosity and tensile properties of specimens produced at different build plate locations. Part densities of specimens manufactured nearest to the powder supply chamber were higher than those of the specimens manufactured nearest to the overflow chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging field of multidisciplinary for design, simulation, and manufacturing optimization is providing technologies that are changing the way designers design [9]. In the medical, aerospace, and automotive fields, the design community is showing great interest in manufacturing many components using AM technology [10,11]. This article has addressed the integration of design and manufacturing problems.…”
Section: Introductionmentioning
confidence: 99%